ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PENGAMBILAN SERTIFIKASI AKUNTANSI - Manik, Ester Sri Noviyanti; Prima, Argo Putra (SCIENTIA JOURNAL, 2023)
The purpose of this study was to examine the effect of motivation on the interest of accounting students intaking accounting certification. The sample in this study is accounting students who are actively registeredat universities in Batam. The method of random sampling is simple using the Slovin formula. The totalrespondents were 301 students from 4 universities in Batam.The method used in data collection is the questionnaire method. The questionnaire used came fromHartutik's research (2016) totaling 41 questions. The hypothesis to be tested is that some independentvariables have a significant positive effect and some have a significant negative effect in predicting theinterest of accounting students in taking accounting certification.The results of this study showed that the variables of quality motivation and social motivation separatelyaffected the variables of student interest significantly positively. While the variables of career motivationand economic motivation separately did not affect the variable of student interest in taking accountingcertification. The independent variables of quality motivation, career motivation, economic motivation, andsocial motivation together have a significant effect on the variable of student interest in taking accountingcertification